2015
DOI: 10.1111/jvim.13807
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of p53 Gene and Its Correlation with the Clinical Outcome in Dogs with Lymphoma

Abstract: Background p53 plays a key role in the apoptotic event induced by chemotherapeutic agents. Mutation of p53 gene has been observed in various spontaneous tumors in humans and is associated with a poor prognosis. p53 abnormalities have been evaluated in several tumors in dogs; however, the association of p53 gene mutation with clinical outcome in dogs with lymphoma has not been documented.Hypothesis/ObjectivesThe aim of this study was to examine p53 mutation in canine lymphoma cells and its association with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…In general, similar to humans, p53 mutations appear deleterious in canines with cancer [7779], suggesting that the tumor suppressor functions are affected. Tumors lacking p53 function were susceptible to HSP90 inhibition by 17-DMAG [80], but again, we do not know the impact of the STAR p53 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, similar to humans, p53 mutations appear deleterious in canines with cancer [7779], suggesting that the tumor suppressor functions are affected. Tumors lacking p53 function were susceptible to HSP90 inhibition by 17-DMAG [80], but again, we do not know the impact of the STAR p53 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Of the seven dogs with a p53 mutation, three had a single base insertion and four had a single base substitution-one of the dogs had a synonymous substitution, but all the other substitutions resulted in a changed amino acid sequence. The study suggests that p53 mutations may not be indicative of a specific anatomical subtype of lymphoma [34]. Furthermore, the study did not account for different histologic or immunophenotypic subtypes, so further exploration with more dogs and more detailed subtype classification is needed to determine a correlation between p53 mutations and subtype of lymphoma.…”
Section: Lymphomamentioning
confidence: 94%
“…The study found that out of 43 dogs with various anatomical subtypes of lymphoma, 7 dogs (16%) had mutations in those exons. More specifically, one dog had a mutation in exons 4, 5 and 6, and two dogs each had a mutation in exon 7 and 8 [34]. Of the seven dogs with a p53 mutation, three had a single base insertion and four had a single base substitution-one of the dogs had a synonymous substitution, but all the other substitutions resulted in a changed amino acid sequence.…”
Section: Lymphomamentioning
confidence: 99%
“…We performed the sequencing technique based on the results and methodology reported by York et al (2012). We analyzed the exons 4 to 8 exons, where the the majority of TP53 gene mutation was related in humans and dogs (MAYR et al, 2002;YONEMARU et al, 2007;KOSHINO et al, 2016). Our results showed no TP53 gene mutations in all canine HCC cases; however, we detect some artefacts (noises) in the chromatograms generated by the Sanger technique.…”
Section: Discussionmentioning
confidence: 76%
“…Hypothesizing that the mutation is in a low percentage of cells, other techniques could be contemplated as the Single Stranded Conformational Polymorphism (HAYASHI, 1991;VELDHOEN et al, 1999;YONEMARU et al, 2007;KOSHINO et al, 2016).…”
Section: Discussionmentioning
confidence: 99%